2021
DOI: 10.1038/s12276-021-00703-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of common neurological disorders by gut microbial metabolites

Abstract: The gut is connected to the CNS by immunological mediators, lymphocytes, neurotransmitters, microbes and microbial metabolites. A mounting body of evidence indicates that the microbiome exerts significant effects on immune cells and CNS cells. These effects frequently result in the suppression or exacerbation of inflammatory responses, the latter of which can lead to severe tissue damage, altered synapse formation and disrupted maintenance of the CNS. Herein, we review recent progress in research on the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 226 publications
0
21
0
Order By: Relevance
“…Since patients with PD have ID, it has been suggested that the GM may be a potential regulator of the pathogenesis of the disease [ 61 ]. In an animal model, PD development was associated with a low expression of bacteria belonging to the taxa Bacteroides , Lactobacillus , Prevotella , Peptostreptococcus , and Butyricicoccus , and a substantial increase in the genera Enterobacter and Proteus spp.…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since patients with PD have ID, it has been suggested that the GM may be a potential regulator of the pathogenesis of the disease [ 61 ]. In an animal model, PD development was associated with a low expression of bacteria belonging to the taxa Bacteroides , Lactobacillus , Prevotella , Peptostreptococcus , and Butyricicoccus , and a substantial increase in the genera Enterobacter and Proteus spp.…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is an early neurodevelopmental disorder with cognitive features, including alterations in communication and social interaction, sensory abnormalities, repetitive behaviors, and variable levels of intellectual disability [ 71 , 72 ]. The etiology of ASD is complex and depends on various genetic and hereditary factors, from changes in chromosome number to maternal age, perinatal hypoxia, and factors related to diet and medication use during fetal pregnancy [ 61 ].…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetate, propionate, and butyrate are among the SCFAs derived mainly from gut microbial fermentation of dietary fibre [63]. SCFA activate G-protein-coupled receptors to modulate neurohumoral gut signalling and exert antimicrobial and anti-inflammatory effects for maintenance of gut integrity and intestinal health [64]. Interestingly, SCFA have direct effects in the brain and may play a role in modulating AD pathogenesis.…”
Section: Short Chain Fatty Acids (Scfa)mentioning
confidence: 99%
“…Research has shown that the gut microbiota modulates psychiatric conditions by producing neurotransmitters, including gamma-aminobutyric acid (GABA), serotonin, melatonin, histamine, acetylcholine, and catecholamines ( Banerjee et al., 2021 ; Morais et al., 2021 ; Zhou et al., 2022 ). Besides the bioactive neurotransmitters, gut microbes also produce short-chain fatty acids (SCFAs), such as propionate, butyrate, and acetate, which can pass through the blood–brain barrier and influence central nervous system (CNS) function by regulating numerous host enzymes, such as histone deacetylases (HDACs) ( Park and Kim, 2021 ). Duan et al.…”
Section: Introductionmentioning
confidence: 99%